(untitled) (Proceedings of the International Conference on Education, 2021)
COVID-19 pandemic forced many changes, including how clinical rotations take place. Reducing face-to-face contact transformed a considerable amount of the activities to distance settings. The residents on the pathology program have a crucial role in the undergraduate medical students’ learning process. To recreate the regular face-to-face contact where members of this learning community would interact, an online one-week rotation on oncologic pathology was designed. The purpose of this study was to explore the perception of undergraduate students of the role of residents as educators on the pathology rotation taught by residents. A quantitative approach considered a cross-sectional and descriptive design to study the phenomenon. The sample consisted of 55 6th-year medical students from a private school in Mexico where the online rotation was taught by residents from July to December 2020. The instrument consisted of a 27-item survey distributed online. Although participants stated they were satisfied with the teaching competence of the residents (mean 4.54), there seems to be a disagreement that the practical part of the sessions, where microscopy techniques are used, should be taught by them (mean 3.84). Students highlighted that they felt more comfortable and relaxed, as well as more confident in asking questions with residents than they did with medical specialists. The resident-student interaction is an enriching learning opportunity for both. Near peer contact found in the residents’ role as educators still needs to be formalized in the curriculum but an initial adaptation done during the pandemic might show its contribution.